POST TRUTH AND ROLE OF INTERNATIONAL RELATION STUDY - Amaritasari Amaritasari; Indah Pangestu (Journal of Social Political Sciences, 2020)
Post truth era is defined as the era when the truth seems right but actually not always correct. It is also an era characterized by media and journalism concerns, especially in the face of false statements by politicians. It flourishes post-truth society, phenomenon, and politics especially when referring to the two big political moments in 2016: The discharge of the United Kingdom from the European Union (Brexit) and the election of Donald Trump as president of the United States. Post truth is also connected with the issue of war on terror where Trump was criticized to be a post-truth and demanded for such response. Thus, security becomes an issue, which is being discussed, debated, and applied in this situation in international relations, which emerge onto deepening and broadening security. One subject that can be the material to support the discussion is the International Relations, which associated with realism and liberalism approach. This paper explores the post truth and analyses using two main approaches of international relation study by extracting and examining the security concepts and terrorism in Asia Region.